TECHNOLOGY FOR THE USE OF MULTIMEDIA TECHNOLOGY IN PRESCHOOL EDUCATIONAL ORGANIZATIONS (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article provides methodological recommendations for the implementation of multimedia technology in the educational process in preschool education.